Integrating TSTS Model into Digital Flipbooks: A Strategy to Foster Numerical and Scientific Problem-Solving Ability - Annisa Fauzana; Suherman; Yerizon; Edwin Musdi (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop and evaluate a Two Stay Two Stray (TSTS)-integrated digital flipbook electronic worksheet (E-LKPD) designed to enhance mathematical problem-solving abilities among eighth-grade students. Employing the Plomp research and development model, the product underwent systematic expert validation, iterative usability testing, and classroom-based field evaluation. Results indicated that both the teaching module and E-LKPD achieved "Very Valid" status, with mean validity scores of 3.47 and 3.54 respectively across content, instructional design, graphics, and language dimensions. Practicality assessments yielded "Very Practical" ratings: 90% for the teaching module and 84.26% for the E-LKPD during field testing. Effectiveness was demonstrated by 80% of students achieving mastery on a mathematical problem-solving assessment, surpassing the predefined 65% success threshold. These findings confirm that integrating the structured TSTS cooperative learning protocol within an interactive digital flipbook format can effectively support the development of mathematical problem-solving competencies. The developed product offers a scalable, curriculum-aligned instructional resource that bridges cooperative pedagogy with technology-enhanced learning.